IMPROVING THE ABILITY TO READ THE AL-QUR’AN WITH THE BITHĀQATU AL-KALIMAH GAME METHOD - Berti Arsyad; Chaterina Puteri Doni; Sriwahyuningsih R. Saleh; Nurul Aini Pakaya; Kholid Mootalu (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
This community service aims to socialize the Bithāqatu al-Kalimah Game method to the community and students at the Al-Ikhlas Recitation Park (TPA) service location in West Pilohayanga Village with the hope that this method can be applied as an effort to increase the interest and enthusiasm of students so that the purpose of learning or mastering al-Al-Qur’an readings Quran can be reached. The method used is the lecture method and card games, the subjects in this service are TPA children. This service is carried out in two phases of activity in the form of an introduction to the Bithāqatu al-Kalimah game method and an evaluation phase in the form of a Bithāqatu al-Kalimah preparation competition. Based on the results of the activity, it can be concluded that the Bithāqatu al-Kalimah game method plays a role in increasing interest and motivation, as well as mastering hijaiyah letters and reading the Al-Qur’an for students.